(untitled) (Medical Forum Monthly, 2022)
Objective: To evaluate diagnostic accuracy of Alvarado score (AS) and Appendicitis Inflammatory Response (AIR) score in the diagnosis of acute appendicitis (AA) in our setup undergoing emergency appendectomy, keeping histopathological findings as gold standard. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the surgical department DHQ Teaching Hospital and Sarhad Surgical Hospital, Kohat, Pakistan from January 1, 2022, to June 30, 2022. Materials and Methods: Total of 204 consecutive suspected cases of AA were included in the study. Alvarado and AIR scores were prospectively calculated and postoperative histopathological confirmation report was obtained for each case. The validity of scoring systems was assessed in terms of sensitivity, specificity, positive predictive value, diagnostic accuracy and area under the receiver operating curve (AUC). Results: The study comprised of 204 patients having mean age of 27.08±11.30 years with 111 (54.41%) males and 93 (45.59%) females. Confirmed cases of AA were seen in 114/119 and 55/85 patients at AS >7 and <7. AIR score >8 and <8 revealed confirmation of AA in 130/134 and 57/68 patients respectively. AS showed sensitivity, specificity, positive predictive value of 64.70%, 88.23%, 96.49% and accuracy of 68.62% while for AIR it was 70.58, 94.11%, 98.36% and 74.50% respectively. Furthermore, AUC for AIR score was found to be better (0.70) than Alvarado score (0.64). Conclusion: Alvarado and AIR scores have fair diagnostic accuracy of approximately 72%. Application of Alvarado and AIR scores for the diagnosis of AA can decrease avoidable radiological and surgical interventions.